Pipistrellus pipistrellus ... - Toffoli, Roberto; Culasso, Paola; Locatelli, Andrea G.; Giraudo, Luca (Zenodo, 2016)
Pipistrellus pipistrellus (Schreber, 1774) Risk Level Europe: Least Concern - LC (Temple & Terry, 2007). Italy: Least Concern - LC (Rondinini et al., 2013). This is the most common species present in the study area. It is found in 75.0% of the kilometric grid, in which the area was divided. It was identified using bioacoustics analysis and roosts survey. Furthermore, it was also caught in mist-nets up to an altitude of 2100 m. Five reproductive roosts were found with a minimum of 21 individuals up to a maximum of 50 and further 6 temporary roosts frequented by single individuals were also identified. In total 34 individuals (21 males and 13 females) were captured in foraging areas and above water bodies. ... : Published as part of Toffoli, Roberto, Culasso, Paola, Locatelli, Andrea G. & Giraudo, Luca, 2016, Bats of Alpi Marittime Nature Park (North West Italy) and Site of Community Importance IT 1160056: distribution and status, pp. 3-13 in Natural History Sciences 3 (1) on page 10, DOI: 10.4081/nhs.2016.254, http://zenodo.org/record/12523731 ...